Improved sensing characteristics of dual-gate transistor sensor using silicon nanowire arrays defined by nanoimprint lithography. Issue 1 (1st January 2017) - Lim, Cheol-Min; Lee, In-Kyu; Lee, Ki Joong; Oh, Young Kyoung; Shin, Yong-Beom; Cho, Won-Ju
Abstract: This work describes the construction of a sensitive, stable, and label-free sensor based on a dual-gate field-effect transistor (DG FET), in which uniformly distributed and size-controlled silicon nanowire (SiNW) arrays by nanoimprint lithography act as conductor channels. Compared to previous DG FETs with a planar-type silicon channel layer, the constructed SiNW DG FETs exhibited superior electrical properties including a higher capacitive-coupling ratio of 18.0 and a lower off-state leakage current under high-temperature stress. In addition, while the conventional planar single-gate (SG) FET- and planar DG FET-based pH sensors showed the sensitivities of 56.7 mV/pH and 439.3 mV/pH, respectively, the SiNW DG FET-based pH sensors showed not only a higher sensitivity of 984.1 mV/pH, but also a lower drift rate of 0.8% for pH-sensitivity. This demonstrates that the SiNW DG FETs simultaneously achieve high sensitivity and stability, with significant potential for future biosensing applications. Abstract :